Pengaruh Endorsement “Tasya Farasya Approved” Terhadap Brand Awareness Produk Somethinc Calm Down Cream (Survei Followers Instagram @tasyafarasya) - Wina Puspita Sari; Muria Putriana; Adi Budi Satrio; Djahwan Kamil; Indira Haniya Arasi; Muhamad Zidan Pahlevi; Muhammad Ihsan Darus; Syahwa Putri Ismaiga (Journal Innovation In Education, 2024)
This study aims to determine the impact of the "Tasya Farasya Approved" endorsement on brand awareness of Somethinc Calm Down Cream, with a case study focusing on the followers of the Instagram account @tasyafarasya. This research employs a quantitative method with an explanatory research types. The Slovin formula and simple random sampling technique were utilized, distributing questionnaires to 100 respondents, with the sample collection conducted online. The data analysis technique used is simple linear regression analysis, performed using SPSS 27 with 50 statements from both variables. The results of this study indicate that the endorsement variable has a positive effect on increasing brand awareness of Somethinc Calm Down Cream skincare products among the followers of the Instagram account @tasyafarasya. The "Tasya Farasya Approved" endorsement label is effective in increasing brand awareness of the Somethinc Calm Down Cream product.